GameStop or game just started? Leveling the playing field for social media meme investors to rebuild the public's trust - Zi Yang (Journal of Risk and Financial Management, 2023)
Against the GameStop frenzy in 2021, this article defines meme investors as a new group of investors in financial markets while demonstrating meme investors' regulatory and social implications. By comparing meme investors with traditional investors under the MiFID II regime, this article finds that meme investors are significantly less wealthy than traditional investors, trade via digital trading platforms, and rely on social media information for investment decision making. This article argues that the emergence of meme investors is an expression of the public's desire for financial inclusion and their frustration with traditional financial institutions. Therefore, properly engaging with meme investors is crucial for rebuilding the public's trust towards regulators. After illustrating meme investors' exposure to default risks, legal uncertainty, and online misinformation, this article calls for regulators to engage with social media meme investors and improve financial literacy among the public.
Keywords: 650; financial literacy; financial inclusion; default risks; public trust; social media meme investors; systemic risks